2021
DOI: 10.26650/connectist2021-000126
|View full text |Cite
|
Sign up to set email alerts
|

Dialogic Communication During Covid-19 Pandemic: An Analysis on Technoparks’ Social Media Usage in Turkey

Abstract: With the outbreak of the Covid-19 pandemic, social media has promptly become an essential communication tool for institutions and organizations to generate and disseminate information as well as building effective dialogue with the public. In this regard, it was vital for technoparks like many other organizations to effectively manage their social media accounts in order to inform and communicate with their stakeholders. Therefore, the current study aims to investigate how technoparks in Turkey used their soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Through content analysis, this study revealed the social media visibility and activity levels of companies operating under technoparks. Although there are many studies in the literature on examining the social media accounts of consumer-oriented businesses with content analysis (Parsons 2013;Peruta and Shields 2018;Shen and Bissell 2013;Vassallo et al 2018), the number of studies revealing the current status of the social media accounts of business-to-business firms is quite low (Aydoğan 2021;Gezginci and Maral 2019;Ubeda et al 2013). Therefore, this research, conducted on companies operating in the technology sector, holds importance as one of the few studies that shed light on the use of social media marketing in industrial markets.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through content analysis, this study revealed the social media visibility and activity levels of companies operating under technoparks. Although there are many studies in the literature on examining the social media accounts of consumer-oriented businesses with content analysis (Parsons 2013;Peruta and Shields 2018;Shen and Bissell 2013;Vassallo et al 2018), the number of studies revealing the current status of the social media accounts of business-to-business firms is quite low (Aydoğan 2021;Gezginci and Maral 2019;Ubeda et al 2013). Therefore, this research, conducted on companies operating in the technology sector, holds importance as one of the few studies that shed light on the use of social media marketing in industrial markets.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…These have predominantly centred on the technoparks rather than directly addressing the companies operating within them. These studies reveal the number of posts and likes on the official social media accounts of Istanbul Technopark and another study that investigates the social media platform used by technoparks during the Covid-19 pandemic, examining the dialogical communication elements present in their posts (Aydoğan 2021;Gezginci and Maral 2019).…”
Section: Introductionmentioning
confidence: 99%